Line positions and energy levels of the 18O substitutions from the HDO/D2O spectra between 5600 and 8800 cm-1 - Mikhailenko S. N. Semen Nikolaevich; Tashkun S. A.; Daumont L.; Jenouvrier A.; Carleer M.; Fally S.; Vandaele A. C. (2010, 2010)
Title screen